Adaptation and psychometric properties of the Junior Eysenck Personality Inventory (JEPI) in Greece - Σ. Αλεξόπουλος Δημήτριος (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The abstract is available in the PDF